Penculikan Anak oleh Orang Tua (Studi Kasus di Pengadilan Negeri Gianyar) - I Komang Oka Raharja; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Konstruksi Hukum, 2020)
Every neglected children must be given protection from institutions or laws which aims at protecting their rights. Children have often been victims of crimes, one of which is kidnapping. Regarding the kidnapping of children, Law Number 35 of 2014 concerning Child Protection stipulates that the incidents of kidnapping and neglected children by parents can cause physical and psychological harms to those neglected children and the unfulfillment of their rights. Therefore, it is necessary to impose criminal sanctions on parents or other people who neglect children. Grounded by this, the problems examined in the present research are: How is the legal protection for children from kidnapping by parents regulated? What are the legal sanctions against parents who commit kidnapping over their children? The research method used in this research is normative juridical, with statutory, conceptual, and case approaches. Data were analysed using a qualitative-normative method. Based on the results of data analysis, the regulation of legal protection for children from kidnapping committed by parents is that every parent shall ensure the fulfillment of children’s rights so that they can live, grow and develop and participate optimally in accordance with human dignity, so that they receive protection from violence and discrimination for the sake of the realisation of Indonesian children who are qualified, noble and prosperous. The legal sanctions against parents kidnapping their children are regulated in Article 330 paragraph (1) of the Criminal Code jo. Article 55 paragraph (1) to 1 KUHP with due observance of Article 330 paragraph (2) KUHP jo. Article 55 paragraph (1) to 1 of the Criminal Code and Law Number 8 of 1981 concerning Criminal Procedure Law and applicable laws and regulations.